THE IMPORTANCE OF THE PERSONAL-ACTIVITY APPROACH IN THE FORMATION OF THE PHYSICAL CULTURE OF THE INDIVIDUAL - Foziljon Mamarozikov (Journal Park Publishing, 2023)
Historically, in all eras, the issue of training in society was the most pressing issue, and even today this issue is one of the main ones. Because the training of members of society is considered to be the power of society that decides the entire existence of its time, that is, its progress, well-being, marifati and manavati, economic stability, the interaction of members of society, the preservation of peace in the world, the joint solution of various attitudes that do not depend on the human factor. The physical culture, which is a component of such an incomparable system, serves in its own way in ensuring the comprehensive perfection and activity of the members of society. Taking this into account, special attention is paid to physical culture in our country, increasing social activity, especially the formation of a personal-activity approach. The article pedagogically investigated the importance of the personal-activity approach to the formation of the physical culture of an individual.
Keywords: Physical Education, Physical Culture, physical education theory, Health, Sports, healthy generation education, healthy lifestyle, physical education system, Personal-Activity, Activity.